2014
DOI: 10.1039/c4cc01312c
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed regio- and stereoselective oxyamination of dienes via tandem aziridination/ring-opening of dienyl carbamates

Abstract: The reaction of dienyl carbamates with PhI(OR)2 in the presence of rhodium catalysts affords vinyl aziridines which are in situ regio- and stereoselectively opened to afford oxyamination products resulting from a selective S(N)2 (Rh2(OAc)4/PhI(OPiv)2) or S(N)2' (Rh2(OPiv)4/PhI(OAc)2) opening. The scope and limitations of this tandem process are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Derivatives (±)‐ 2 a – 4 a , with Bz, Ac and Piv protecting groups, were synthesised from carbamate 1 , Rh 2 (OAc) 4 catalyst and the appropriate PhI(OR) 2 reagent under the optimised reaction conditions for S N 2 aziridine opening. In this case, catalyst and base play a determining role in the efficiency and selectivity (S N 2 versus S N 2′) of the oxyamination reaction . Alternatively, PhIO‐mediated intramolecular aziridination of carbamate 1 was applied for the preparation of compounds (±)‐ 5 and (±)‐ 6 , with a mixture of water in acetonitrile or methanol, respectively, as nucleophiles for the ring‐opening step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Derivatives (±)‐ 2 a – 4 a , with Bz, Ac and Piv protecting groups, were synthesised from carbamate 1 , Rh 2 (OAc) 4 catalyst and the appropriate PhI(OR) 2 reagent under the optimised reaction conditions for S N 2 aziridine opening. In this case, catalyst and base play a determining role in the efficiency and selectivity (S N 2 versus S N 2′) of the oxyamination reaction . Alternatively, PhIO‐mediated intramolecular aziridination of carbamate 1 was applied for the preparation of compounds (±)‐ 5 and (±)‐ 6 , with a mixture of water in acetonitrile or methanol, respectively, as nucleophiles for the ring‐opening step.…”
Section: Resultsmentioning
confidence: 99%
“…In 2001, Donohoe and co‐workers reported the oxyamination of 2,4‐dien‐1‐yl carbamates with osmium reagents to afford 2‐aminopent‐4‐en‐1,3‐diol derivatives (Scheme a) . Recently, we demonstrated that rhodium‐catalysed intramolecular aziridination of dienyl carbamates in the presence of PhI(OR) 2 afforded vinylaziridines, which were opened in situ by the OR group released after formation of the nitrene transfer reagent. The regioselectivity of this process (S N 2 versus S N 2′) was controlled by properly selecting the catalyst and PhI(OR) 2 reagent (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Addition of the metallanitrene to the glycal π bond provides a glycosyl aziridine (e.g., 8 in the 3- β series), possibly with the metal still complexed at nitrogen (not shown). 50 As long as the N−anomeric contact is present, the acceptor adds in S N 2 fashion, leading to the 1,2-trans amidoglycosylation ( AG ) product. Dihydropyranone ( DHP ) byproduct formation, meanwhile, also originates from the metallanitrene intermediate 7 , as supported by our previous studies that utilized an alternative N -tosyloxycarbamate nitrene precursor (which obviates the need for a hypervalent iodine oxidant) and gave the same distribution of amidoglycosylation and C3−H oxidation products with rhodium catalysis as compared to the standard primary carbamate using PhIO.…”
Section: Discussionmentioning
confidence: 99%
“…7 In another example, rhodium-catalyzed amino oxygenation was achieved with chemo- and site-selectivity through a diene-tethered nitrogen group yet gave a nearly equal mixture of 1,2- and 1,4-addition products. 8 Despite these seminal developments, a three-component modular and selective amino oxygenation reaction incorporating a diverse range of 1,3-dienes remains lacking, and is greatly desired. 9…”
Section: Introductionmentioning
confidence: 99%